(untitled) (Research, Society and Development, 2020)
Aging is defined as a process of organic and functional decline that unavoidably happens as time passes; chronic diseases, in turn, are diseases that persist for longer than six months and are not solved within a short period; palliative care, on the other hand, is an ensemble of medical care measures that aim to improve an ill person and their family’s quality of life, relieving and preventing suffering in face of an illness. Nowadays, more and more frequently, palliative care is being used to deal with chronic situations and not only the end of the life, therefore, this assay’s objective is to verify how articles approach the subject of palliative care associated with chronic deseases on advanced age. This assay is an Integrative Review, with narrative approach. To answer this assay’s guiding question, a search was carried out in the BVS-Birreme, MedLine, Lilacs, Scielo and BMC, databases, using the terms: “Palliative Care”, “Aging” and “Chronic Disease”. The results of this research highlight the importance present in palliative care used to control chronic diseases, and emphasize its relevance in situations where the patient is an elderly with a chronic disease. Despite this, the articles more comonly consider palliative care, even if related to chronic diseases, as a comfort method to prepare the elderly for the end of life.